Standardization of a Newly Fabricated Multicompartment Model to Evaluate Analgesic, Antipyretic and Anti-inflammatory Action of a Drug - Dumbwani, Jacky; K. Jain, Neetesh (Journal of Neonatal Surgery, 2025)
In the research work a design of a multiple compartment model was successfully fabricated. The purpose of present study is to standardize the model by comparing the results obtained from the traditional and standard model for analgesic, antipyretic and anti-inflammatory activity with the results obtained from the newly fabricated multicompartment model. Many drugs have more than one action and evaluation of one action of a drug requires one whole screening model whereas for the evaluation of other action of same drug will require one more different screening model. In this study a new model has been fabricated for the evaluation of three different actions of one drug. Aspirin has analgesic, antipyretic, anti-inflammatory, and antiplatelet activity. Evaluation of all the activities of aspirin, we will require four different methods and models but in our study the newly fabricated model alone will be able to evaluate three actions of a single drug. A detailed analysis of data was performed by applying statistics on the data collected from both the ways